The genetics of phenotypic plasticity in plant defense: trichome production in Mimulus guttatus - Holeski, L. M.; Chase-Alone, R.; Kelly, J. K.
Insect herbivory is a major driving force of plant evolution. Phenotypic plasticity and developmental variation provide a means for plants to cope with variable herbivory. We characterized the genetics of developmental variation and phenotypic plasticity in trichome density, a putative defensive trait of Mimulus guttatus (yellow monkeyflower). Our results are evaluated in relation to the optimal defense theory, which provides testable predictions for plastic and developmental patterns in defense traits. We found that both developmental stage and simulated insect damage affected trichome production, but in different ways. Plants were more likely to produce at least some trichomes on later leaves than on earlier leaves, regardless of damage. Damage did not affect the average probability of producing trichomes, but it did increase the density of hairs on trichome?positive plants. We mapped trichome quantitative trait loci (QTL)by selectively genotyping a large panel of recombinant inbred lines derived from two highly divergent populations. Several highly pleiotropic QTL influenced multiple aspects of the trichome phenotype (constitutive, developmental, and/or plastic responses). Only one of the QTL influenced trichome induction following damage. In a result that is consistent with a central prediction of optimal defense theory, the high allele at this location was from the ancestral population with low constitutive trichome production.
Keywords: PHENOTYPE PLASTICITY; MIMULUS GUTTATUS; QTL; TRICHOMES; TRADE-OFF, OPTIMAL DEFENSE THEORY